ANALYSIS OF STUDENTS’ ABILITY IN USING MODIFIER ON WRITING PARAGRAPH - Ginting, Fiber Yun A (Universitas Katolik Santo Thomas Medan, 2024)
The aim of this study is to analyze the students’ ability in using modifiers on writing paragraphs. The design of this research is descriptive qualitative because the result of this study is used as a problem-solving procedure of the observed things by describing the research objects when the research is done based on the facts found. The results of this study show that, the dominant type of modifier in the provided sentences is the adjective modifier, which occurs more frequently compared to the adverb modifier. This indicates a higher usage of descriptive words that modify nouns rather than verbs or actions. Adjectives were found to be the most frequently used type of modifier, suggesting a focus on descriptive language. The conclusion in this study is the examination revealed that adjective modifiers were used significantly more frequently, with 15 instances compared to 5 instances of adverb modifiers. This dominance of adjective modifiers indicates a strong tendency towards descriptive language that enhances the specificity and detail of nouns within the text.